Holocene reconstruction of the spruce budworm outbreak-fire interaction in the mixed boreal forest reveals a peculiar oscillation - Leclerc, Marc-Antoine; Simard, Martin; Morin, Hubert (Frontiers in Ecology and Evolution, 2025)
Characterizing millennial and multi-millennial variability in disturbance regimes will be crucial in improving knowledge within the context of a changing climate and the development of sustainable forest management practices in the eastern Canadian mixed boreal forest. The major biotic and abiotic disturbances in the mixed boreal forest are the spruce budworm, and fire, respectively. The ability to reconstruct the variability of these disturbance agents under different climate conditions over long time periods will help elucidate the interaction between the agents and their dynamics in the mixed boreal forest. The objective of this observational study was to reconstruct the frequency of large spruce budworm population (LSBP) and fire disturbance events, and describe their interaction in the mixed boreal forest over the course of the Holocene within the context of changing vegetation and climatic conditions. Lepidopteran scales and sedimentary charcoal were used to reconstruct the local/extra-local disturbance history from lake sediment along with pollen to reconstruct changes in tree species composition. Spruce budworm and fire disturbance events were determined using the CharAnalysis software. Regime shifts in disturbance event frequencies along with changes in tree composition were detected using Sequential T-test Analysis of Regime Shifts. Spearman’s correlation was used to determine the relationship between spruce budworm and fire event frequencies. Over the course of the Holocene, 57 LSBP events and 76 fire events were detected with event frequencies ranging between 0.75-6.30 events*kyr-1 and 1.71-10.5 events*kyr-1 respectively. Nine and 7 regime shifts in LSBP and fire event frequencies were detected respectively, along with 2 shifts in vegetation. A significant negative correlation was observed between LSBP and fire event frequencies from 6000-1000 BP suggestive of a linked disturbance interaction. The first local lake sediment multi-millennial disturbance regime reconstruction comprising both spruce budworm and fire in the mixed forest revealed a very peculiar oscillation in disturbance event frequencies. Each disturbance seemingly establishes a positive disturbance-vegetation feedback that favors itself and inhibits the occurrence of the other. Further, rapid climate change events may act as a key trigger in establishing the respective feedback loops resulting in the observed disturbance event frequency oscillation.